Target Site Insensitivity Detection in Deltamethrin Resistant Culex pipiens Complex in Iran - Reza ZEIDABADINEZHAD; Hassan VATANDOOST; Mohammad Reza ABAI; Navid DINPARAST DJADID; Abbasali RAZ; Mohammad Mahdi SEDAGHAT; Mohamad Ali OSHAGHI; Ahmad RAEISI; Neda ADIBI (Iranian Journal of Public Health, 2019)
Background: Some mosquito species which belong to the Culex. pipiens complex are primary vectors for West Nile virus, Sindbis, Dirofilaria immitis, and many arboviruses. Knockdown resistance (kdr) mutations in the voltage-gated sodium channel (VGSC) gene of Cx. pipiens that is inherited, is one of the important threats for the efficacy of pyrethroids insecticides. Knockdown resistance (kdr) mutation, L1014F, is a well-defined mechanism of resistance to pyrethroids and DDT in many insect species. The aim of study was to determine the mechanisms of Insecticide resistance in this species